Simulation of Biosynthesis Gas Process from Palm Oil Mill Effluent Sewage by Aspen HYSYS and SuperPro Designer - Seyyed Hamid Esmaeili‑Faraj; Mehrab Rezazadeh; Jafar Abdi (آب و فاضلاب, 2023)
In this work, the process of biogas production from palm oil factory effluent was simulated and then the produced biosynthetic gas was sweetened. For this purpose, the biogas production process from wastewater treatment was simulated using SuperPro Designer v9.0 software. Then, the resulting biogas entered the chemical absorption and reforming sections for sweetening and conversion to syngas, respectively, and these steps were simulated with Aspen HYSYS v11.0 software. The simulation results of the first stage showed that the effluent feed of this factory with a flow rate of 42000 kg/h and COD of 62000 mg/L leads to the production of 1786 kg/h biogas containing various compounds such as methane, carbon dioxide, hydrogen sulfide and water with the molar fraction of 0.446, 0.245, 0.178 and 0.040, respectively. In the chemical absorption section, MEA solvent 10 %wt. and solvent-to-gas molar ratio of 13.51 were used, which led to the efficient removal of CO2 and H2S up to 1 ppm and 99.99%, respectively. The examination of temperature changes in the absorption tower also showed that the temperature increases along the absorption tower. In the methane steam-reforming unit, two different strategies were used: 1) plug flow reactor (with fluid package of Peng-Robinson-Stryjek–Vera) and 2) conversion and equilibrium reactors (with fluid package of Peng-Robinson). The results showed that the purity of hydrogen in the biogas produced in the second strategy (conversion and equilibrium reactors) was higher than the first one (plug flow reactor), and on the other hand, the purity of CO2 was zero in the second strategy.